Erratum: The Demand for Effective Charter Schools - Walters, Christopher (Journal of Political Economy, 2019)
Previous articleNext article FreeErratumErratum: The Demand for Effective Charter SchoolsChristopher WaltersChristopher WaltersUniversity of California Berkeley Search for more articles by this author Original articleThe Demand for Effective Charter SchoolsPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreThis note documents an error in “The Demand for Effective Charter Schools,” published in volume 126, number 6 (December 2018) of this Journal. In Section IV.A, the expression +max{h−1(c(Xi)/π1),ξi1} incorrectly appeared in four places: equation (12), equation (13), and two unnumbered equations on page 2194. This expression should instead read −max{h−1(c(Xi)/π1),−ξi1}.The corrected equation (12) should therefore readv1(Xi,Di1,Di0)+ψi1−max{h−1(c(Xi)/π1),−ξi1}>0.The corrected equation (13) should readIV(x,d)=μ1(x)−μ0(x)+E[g1(ψi1)−g0(ψi0)|v1(x,d1,d0)+ψi1−max{h−1(c(Xi/π1),−ξi1}>0].The corrected equation in the middle of page 2194 should readlimd→d*IV(x,d)=μ1(x)−μ0(x)+E[g1(ψi1)−g0(ψi0)|ψi1−max{h−1(c(Xi/π1),−ξi1}>−∞],and the corrected equation at the bottom of page 2194 should readψ¯1(x,d)≡E[ψi1|v1(x,d1,d0)+ψi1−max{h−1(c(x)/π1),−ξi1}>0].This error does not affect the accuracy of any results or text in the paper. Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 127, Number 2April 2019 Article DOIhttps://doi.org/10.1086/703048 HistoryPublished online March 07, 2019 © 2019 by The University of Chicago. All rights reserved.PDF download Crossref reports the following articles citing this article:Jack Mountjoy Community Colleges and Upward Mobility, SSRN Electronic Journal (Jan 2019).https://doi.org/10.2139/ssrn.3373801Related articlesThe Demand for Effective Charter Schools30 Oct 2018Journal of Political Economy